Ultra-processed food hazard education for students of SMK Manbaul Ulum, Cirebon - Renny Amelia; Muh. Yani Zamzam; Revi Maulid Nabilla; Muhammad Gabriel; Windi Bina Lestari; Siti Aisyah Fitri; Chaerunnisa Febria Wibowo; Anisa Devi Rosalinda; Tria Ananda; Najwa Firdausy Salsabila; Azzahra Nur Auralia; Elvania Rahma Dina Safitri; Zidane Pratama Yunargi (Community Empowerment, 2024)
People tend to consume high-fat foods such as fast food. The purpose of this community service activity is to determine the habits of consuming fast food and to increase students' knowledge about healthy and balanced food at SMK Manbaul Ulum. The method used is through education to students of SMK Manbaul Ulum. The results of the activity showed that education about the dangers of junk food succeeded in increasing knowledge by 6.4%.